Pituitary Involvement in Granulomatosis with Polyangiitis: A Retrospective Analysis in a Single Chinese Hospital and a Literature Review - Shixuan Liu; Yan Xu; Naishi Li; Shi Chen; Shangzhu Zhang; Linyi Peng; Wei Bai; Jinglan Wang; Jinming Gao; Xiaofeng Zeng; Juhong Shi; Mengzhao Wang (International Journal of Endocrinology)
Purpose. Granulomatosis with polyangiitis (GPA) is an anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis that can involve virtually many organs, including the pituitary. Pituitary involvement in GPA is rare, with only case reports or small case series published previously. Methods. We used the electronic medical record system in our hospital to identify four patients of pituitary involvement in GPA. We summarized the clinical characteristics, radiographic findings, treatments, and clinical outcomes of the four patients. We further performed a systematic literature review of 66 GPA cases with pituitary involvement that were published on the PubMed database. Results. The four women in our report were between 57 and 73 years of age. All patients had pituitary abnormalities on radiology; three developed diabetes insipidus (DI). All patients had multisystem involvement. After treatment with glucocorticoids and cyclophosphamide (CYC), all patients showed clinical improvement but pituitary function did not resume. Literature review identified 66 additional patients with pituitary involvement in GPA; diabetes insipidus (57/66, 86.4%) and hypogonadism (34/66, 51.5%) were the most frequent pituitary disorders, and the most frequent imaging lesion was an enlarged pituitary (25/64, 39.1%). After treatment with corticosteroids and/or immunosuppressive agents, most patients (45/66, 68.2%) developed remission from systemic disease, 13 patients (13/57, 22.8%) showed remission of DI, and 8 patients (8/46, 17.4%) showed remission of hormone deficiencies. Conclusions. GPA should be carefully considered as a potential cause of pituitary dysfunction (PD), especially when multisystem dysfunction exists. Conventional treatment with corticosteroids and/or immunosuppressive agents improves systemic symptoms, but pituitary disorders persisted in most patients.